Photographic evidence of dholes in Gunung Gede Pangrango National Park, Indonesia. - Anton Ario (Universitas Pakuan, 2023)
For many years the dhole was believed to have been undetected in Gunung Gede Pangrango National Park (GGPNP). Nevertheless, in 2012 and 2013, we were able to photograph this elusive creature. We report the photographic evidence of the endangered dhole (Cuon alpinus) using camera trap di GGPNP.